2010
DOI: 10.1007/s11606-010-1385-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Chronic Illness Care Education (ACIC-E): A Tool for Tracking Educational Re-design for Improving Chronic Care Education

Abstract: The ACIC-E instrument proved feasible to complete. Participating teams, on average, recorded modest improvement in all areas measured by the instrument over the duration of the collaboratives. The relationship between the final ACIC-E score and the number of educational measures was weak. Further research on its utility and validity is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…7,8 Research has revealed a fundamental gap in student learning of SMS across many health professions. [9][10][11][12][13][14] If HCPs are not equipped with the necessary skills to guide their patients, patients might not adhere to their programmes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Research has revealed a fundamental gap in student learning of SMS across many health professions. [9][10][11][12][13][14] If HCPs are not equipped with the necessary skills to guide their patients, patients might not adhere to their programmes.…”
mentioning
confidence: 99%
“…[7][8][9][14][15][16] In pursuit of this objective, several academic medical centres across the United States adopted a national initiative aimed at incorporating CCM programmes; this initiative has shown promising results and inspired further initiatives. [7][8][9]17 On a smaller scale, incorporating SMS into educational curricula has been successful in improving students' knowledge of SMS. 14,18 Another study evaluating web-based SMS training for medical residents found an increase in professional beliefs and confidence in the use of SMS.…”
mentioning
confidence: 99%
“…An instrument was developed specifically for this purpose-the Assessment of Chronic Illness Care for Education (ACIC-E), which tracked the extent of educational engagement and redesign that addressed the same 7 components of the CCM described above for the ACIC. This instrument, a direct modification of the ACIC with a focus on specific changes in the education program, is described in detail elsewhere 13 . It was employed in the Collaboratives in the same way as described for the ACIC above.…”
Section: Study Of the Intervention And Methods Of Evaluationmentioning
confidence: 99%
“…Health care team meetings generally included residents' input in planning for care delivery. Structured mentored experiences were developed for selected components of the CCM that are not usually 13,14 , and they were implemented in the latter half of the assessment period of the national Collaborative, while the California Collaborative employed the ACIC-E and the two educational measures to track their progress from the outset of the assessment period. The results for the California initiative are presented as change scores from baseline in the ACIC-E (Fig.…”
Section: Education Measuresmentioning
confidence: 99%
“…Some residency training programs have reported work in redesigning their curricula and clinical components to train residents to engage with chronically ill patients and to measure their proficiency in doing so [8,9]. Previous publications have also described curricula that address individual components of the PCMH, such as pain management [10], team-based care [11] and group visits [12].…”
Section: Introductionmentioning
confidence: 99%